PIM achievements in innovations related to inclusive and efficient agricultural value chains - de Brauw, Alan; Bulte, Erwin (International Food Policy Research Institute, 2021)
Efforts to promote the development and agricultural value chains area common element of strategies to stimulate economic growth in low-income countries. Since the world food price crisis in 2007-2008, developing country governments, international donor agencies, and development practitioners have placed additional focus on trying to make agricultural value chains work better for the poor. As value chains evolve to serve new markets, they tend to become less inclusive. For example, if a value chain for high quality rice arises within an economy, it is inherently easier for those who sell rice to retailers to source that high quality rice from larger farms with the ability to control quality than from dozens of smallholder farms. As a result, the normal path of value chain evolution can be biased against smallholders; hence it is important to understand what types of interventions can make value chains more inclusive while also making them more efficient.